2007
DOI: 10.1016/j.bbrc.2007.10.098
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of an α-enolase of the oral pathogen Streptococcus mutans that binds human plasminogen

Abstract: Streptococcus mutans is the etiologic agent of dental caries and is a causative agent of infective endocarditis. While the mechanisms by which S. mutans cells colonize heart tissue is not clear, it is thought that bacterial binding to extracellular matrix and blood components is crucial in the development of endocarditis. Previously, we have demonstrated that S. mutans cells have the capacity to bind and activate plasminogen to plasmin. Here we report the first cloning and characterization of an alpha-enolase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…More importantly, virulent factor released from denture plaque is known to be a significant risk factor for opportunistic infections and aspiration pneumonia especially in elderly people and in individuals who are immunocompromised 15) . Streptococcus mutans is regarded as a major etiological agent of dental caries 16) while Candida is a common bacteria which may cause Candida-associated denture stomatitis 17) . Thus, a restorative material that possesses antibacterial properties and inhibits bacterial growth around the restoration would be desirable.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, virulent factor released from denture plaque is known to be a significant risk factor for opportunistic infections and aspiration pneumonia especially in elderly people and in individuals who are immunocompromised 15) . Streptococcus mutans is regarded as a major etiological agent of dental caries 16) while Candida is a common bacteria which may cause Candida-associated denture stomatitis 17) . Thus, a restorative material that possesses antibacterial properties and inhibits bacterial growth around the restoration would be desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Enolase was identified as a multifunctional protein, involved in the pathogenicity in several Streptococcus by binding the plasminogen of an infected host, 13,14 including the bacterial migration across the mammalian extracellular matrix, 15 and an important antigen using immunoproteomics analysis of extracellular and cell-wall associated proteins of SS2. 16,17 So far, several reports have shown that the enolase of several types of GC bacteria could activate plasminogen and then the surface-bond plasmin could degrade extracellular matrix and laminin, and facilitate penetration of the organism through reconstituted basement membrane, 18 suggesting that anti-Enolase antibodies could be important as an adjunctive vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant S. mutans fibronectin-binding protein (rSmFnB) was purified from 1 liter cultures induced and processed using denaturing conditions as described previously using the Qiagen protocol [26]. To determine the purity of eluted protein, samples collected from the metal affinity column were separated on a 10% SDS-PAGE gel and transferred onto a nitrocellulose membrane and probed with mouse anti-His antibodies.…”
Section: 4expression and Purification Of S Mutans Fibronectin-binmentioning
confidence: 99%